2005
DOI: 10.1017/s1355770x05002263
|View full text |Cite
|
Sign up to set email alerts
|

National environmental performance: an empirical analysis of policy results and determinants

Abstract: Efforts to identify the determinants of environmental policy success have largely been anecdotal and case study based. This article seeks to shift environmental policy analysis on to more analytically rigorous and empirical foundations. Using statistical analysis, we identify a set of factors that drive environmental performance as measured by levels of urban particulates, sulfur dioxide, and energy use per unit of GDP. Although the data are imperfect and causal linkages cannot be definitively established, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 14 publications
3
72
0
1
Order By: Relevance
“…Economic theory suggests that control of pollution improves as a country develops, and thus, rich countries not only can, but should, invest in pollution control and other environmental improvements [22]. With the same criteria, Jahn [23] considers that countries with greater economic growth are better able to handle environmental problems, because they have the financial resources to do so.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic theory suggests that control of pollution improves as a country develops, and thus, rich countries not only can, but should, invest in pollution control and other environmental improvements [22]. With the same criteria, Jahn [23] considers that countries with greater economic growth are better able to handle environmental problems, because they have the financial resources to do so.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…With respect to the first theory, Esty and Porter [22] found a significant relation between income and environmental performance, suggesting that the alleviation of poverty should be considered a priority in environmental policy; nonetheless, some authors argue that the ecological Kuznets curve theory is only valid for a small class of environmental impacts and may not be applicable to developing countries [24]. According to Dinda [25], environmental pressure increases more rapidly than income in the initial stage of development and then decreases in relation to growth in GDP at higher income levels.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies it is stated that the increases in three components of the financial structure, namely profit rate (Brammer and Pavelin, 2008;Hontou et al, 2007;Wagner and Schaltegger 2004), financial resources (Brammer and Pavelin, 2008;Clausen et al, 2003;Hamans, 2009a;Hoffman, 2000;Orsato, 2006;Wagner and Schaltegger 2004) and turnover (Wagner and Schaltegger, 2004) increases the environmental sensitivity of firms. Furthermore, it has been considered that the increases in two components of the organizational structure, number of employees (Brammer and Pavelin, 2008;Clausen et al, 2003;Delmas and Toffel, 2004;Esty and Porter, 2005;Henri and Journeault, 2008a;Sarmentoa et al, 2007;Wagner and Schaltegger 2004) and level of institutionalizing, leads (directs) firms toward environmental management. Thus, with the effect of the past performance of a firm, the environmental sensitivities and intentionality of managers of such firms to environmental management implementations will increase.…”
Section: The Firm's Past Performancementioning
confidence: 99%
“…On the other hand, common sense and recent studies prove that increased wealth is a prerequisite for environmental improvements (Grossman and Krueger 1995). Several empirical studies have likewise shown that wealth is an important factor in explaining environmental policy results, but not alone determinative of environmental policy (Esty and Porter 2005).…”
Section: V5 Gaps In Environmental Performancementioning
confidence: 99%